2013
DOI: 10.11609/jott.o2806.484
|View full text |Cite
|
Sign up to set email alerts
|

Ecological observations on the Indian Spiny-tailed Lizard Saara hardwickii (Gray, 1827) (Reptilia: Squamata: Agamidae) in Tal Chhapar Wildlife Sanctuary, Rajasthan, India

Abstract: Abstract:Observations on the Indian Spiny-tailed Lizard Saara hardwickii (Gray, 1827) were undertaken in Tal Chhapar Wildlife Sanctuary, Rajasthan, India during the monsoons (July) following quadrat sampling that was time-constrained. The study revealed that the area is one of the preferable habitats for the species. A population analysis showed that the relative abundance of the subadults was higher, followed by juveniles and adults during the study period. The beginning of activity of the lizards was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Most importantly from MSA, all the sequences generated in this study found to be monomorphic. Since this species is conservation dependent and in India currently it exists in small pocket populations in northwestern part [14][15][16][17][18][19][20][21][22][23] , DNA sequence monomorphism suggests that there is an urgent need of conservation of this species in its present distribution in northwestern India. However, this cannot be completely ascertained from this study because of the small sample size and thus study with large sample size might be useful for more accurate population genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most importantly from MSA, all the sequences generated in this study found to be monomorphic. Since this species is conservation dependent and in India currently it exists in small pocket populations in northwestern part [14][15][16][17][18][19][20][21][22][23] , DNA sequence monomorphism suggests that there is an urgent need of conservation of this species in its present distribution in northwestern India. However, this cannot be completely ascertained from this study because of the small sample size and thus study with large sample size might be useful for more accurate population genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…the Thar desert of Rajasthan and Gujarat [14][15][16][17][18][19][20][21][22] . Recently, one small population of this species is reported from the Sariska National Park [23] , which at present is the only known population of this species in Rajasthan outside the Thar desert area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body fat stored in the tail assumed to have medicinal value as it is boiled down and oil is used as a cure for impotence and embrocation. These lizards are frequently used in different parts of Pakistan and India for medicinal purpose [7]. Due to illegal trade and habitat destruction; this species is threatened.…”
Section: Introductionmentioning
confidence: 99%